2006
DOI: 10.1177/1077558706287003
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know about Health Care Team Effectiveness? A Review of the Literature

Abstract: This review of health care team effectiveness literature from 1985 to 2004 distinguishes among intervention studies that compare team with usual (nonteam) care; intervention studies that examine the impact of team redesign on team effectiveness; and field studies that explore relationships between team context, structure, processes, and outcomes. The authors use an Integrated Team Effectiveness Model (ITEM) to summarize research findings and to identify gaps in the literature. Their analysis suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
723
0
25

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(768 citation statements)
references
References 57 publications
20
723
0
25
Order By: Relevance
“…In contrast, other research evaluated single sites and most commonly reported wait times only (Baliski et al., 2014; Oon et al., 2014; Royle et al., 2014). The findings are similar to those of a systematic review of health‐care team effectiveness literature from 1985 to 2004 which found that the type and diversity of clinical expertise involved in team decision making largely accounted for improvements in patient care and organisational effectiveness, while collaboration, conflict resolution, participation and cohesion were most likely to influence staff satisfaction and perceived team effectiveness (Lemieux‐Charles & McGuire, 2006). This suggests that measures reflecting individual provider, team and patient‐reported outcomes should be used to assess the effectiveness and impact of DAPs in addition to more traditional measures such as wait times.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, other research evaluated single sites and most commonly reported wait times only (Baliski et al., 2014; Oon et al., 2014; Royle et al., 2014). The findings are similar to those of a systematic review of health‐care team effectiveness literature from 1985 to 2004 which found that the type and diversity of clinical expertise involved in team decision making largely accounted for improvements in patient care and organisational effectiveness, while collaboration, conflict resolution, participation and cohesion were most likely to influence staff satisfaction and perceived team effectiveness (Lemieux‐Charles & McGuire, 2006). This suggests that measures reflecting individual provider, team and patient‐reported outcomes should be used to assess the effectiveness and impact of DAPs in addition to more traditional measures such as wait times.…”
Section: Discussionsupporting
confidence: 82%
“…physically side by side/face to face). 23,222 However, the concept of 'team' in healthcare is rapidly evolving to include a greater emphasis on interprofessional collaboration, 223 as well as new team structures. With the advent of restricted duty hours, 224 and frequent hand-offs, 29,30 team members are often working in shifts [225][226][227] and are also becoming dispersed geographically.…”
Section: Discussionmentioning
confidence: 99%
“…15 Prior reviews have examined teamwork training and interventions, as well as the outcomes of effective teams. 1,[16][17][18][19][20][21][22][23][24] These reviews have advanced the understanding of 'what works' to improve teamwork (i.e. curricula and interventions), but they do not fully answer the critical question of how teamwork is best measured in healthcare.…”
mentioning
confidence: 99%
“…Most studies of team structure within both the cancer-related and general health-care delivery literatures tend to conceptualize team structure as either team composition (24,25) or team size (26). Generally, the influence of both variables on team performance or patient outcomes is mixed.…”
Section: Team Structurementioning
confidence: 99%